CORRELATION OF ENVIRONMENTAL AND SOCIO-ECONOMIC FACTORS IN THE TRANSITION TO A "GREEN ECONOMY" - Imamxodjayeva Aziza Anvarovna (American Journals, 2024)
Uzbekistan faces significant environmental challenges as it seeks to transition to a green economy. This study analyzes the correlation between environmental and socio-economic factors in Uzbekistan's green economic transition. Linear regression analysis of economic, social, and environmental indicators from 2022-2024 revealed that renewable energy consumption and energy efficiency are positively correlated with GDP growth and HDI, while carbon intensity and pollution are negatively correlated. The results suggest that investing in clean energy and environmental protection can drive sustainable socio-economic development in Uzbekistan. However, challenges remain in terms of financing, infrastructure, and changing behaviors and mindsets. The government should prioritize green stimulus spending, capacity building, and public awareness to accelerate the green transition in an inclusive manner. Further research is needed on green jobs, eco-innovation, and climate-resilient development in the Uzbek context.
Keywords: Green economy, sustainable development, Uzbekistan, environmental policy, energy transition